Sodium-ion battery positive electrode material precursor, preparation method thereof, positive electrode material and battery

By using the core-transition layer-shell structure design in the positive electrode material of sodium ion battery, and using copper oxalate and ferromanganese hydroxide, the problem of insufficient density and electrical performance of the existing sodium ion battery is solved, and the problem of insufficient density and electrical performance of the positive electrode material of existing sodium ion battery is achieved. High energy density and uniform elemental distribution.

CN119324211APending Publication Date: 2025-01-17GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411358412.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The tap density of existing sodium ion battery positive electrode materials is low, resulting in insufficient energy density, and the nickel ferromanganese copper hydroxide products have many lattice defects and high impurity content, which affects electrical performance.

Method used

The precursor of the cathode material for sodium ion batteries was prepared using a segmented co-precipitation method. A copper hydroxide transition layer was grown on the copper oxalate core, and a nickel iron manganese hydroxide shell was grown in situ on the transition layer to form a dense core and a loose core. Structure of transition layer and shell.

Benefits of technology

The tap density and electrical properties of the positive electrode material of sodium ion battery are improved, the energy density is enhanced, and the preparation process is simplified for easy operation and implementation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324211A_ABST
    Figure CN119324211A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion batteries, and discloses a sodium-ion battery positive electrode material precursor, a preparation method thereof, a positive electrode material and a battery. The sodium ion battery positive electrode material precursor comprises an inner core, a transition layer and a shell layer, the porosity of the inner core is smaller than that of the transition layer, the transition layer comprises copper oxide, and the shell layer comprises nickel-iron-manganese hydroxide. According to the invention, a segmented coprecipitation method is adopted to synthesize the sodium-ion battery positive electrode material precursor with a core-shell structure and high tap density, so that the energy density of the sodium-ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery positive electrode material precursor, a preparation method thereof, a positive electrode material and a battery. Background Art

[0002] With the consumption of energy, the scarcity and high price of lithium resources cannot meet the needs of large-scale energy storage in the future, and the commercial development of sodium-ion batteries has gradually come into people's view. The capacity of sodium nickel iron manganese oxide positive electrode materials can not only catch up with lithium iron phosphate materials, but also has price advantages, and has a certain alternative to lithium batteries. Generally speaking, the cycle performance and air stability of sodium nickel iron manganese oxide positive electrode materials are poor, and they often need to be doped and modified. For example, doping with copper elements can stabilize the structure, inhibit phase change, and improve its electrical properties. Compared with doping copper in the stage of synthesizing positive electrode materials, doping in its precursor stage to prepare nickel iron manganese copper hydroxide is beneficial to improve the uniformity of element distribution when synthesizing positive electrode materials, and thus is beneficial to improve the electrical properties of sodium nickel iron manganese oxide positive electrode materials. However, the conventional co-precipitation method is used to synthesize nickel iron manganese copper hydroxide. Due to the reasons that the precipitation coefficient and crystal structure of copper hydroxide are not compatible with nickel iron manganese hydroxide, the nickel iron manganese copper hydroxide product has more lattice defects, high impurity content, and low density.

[0003] In view of this, the present invention is proposed. Summary of the invention

[0004] The object of the present invention is to provide a sodium ion battery positive electrode material precursor, a preparation method thereof, a positive electrode material and a battery, aiming to increase the tap density of the sodium ion battery positive electrode material precursor, thereby increasing the energy density of the corresponding sodium ion battery.

[0005] The present invention is achieved in that:

[0006] In a first aspect, the present invention provides a sodium ion battery positive electrode material precursor, which comprises a core, a transition layer and a shell layer, wherein the porosity of the core is less than the porosity of the transition layer, the transition layer comprises copper oxide, and the shell layer comprises nickel iron manganese hydroxide.

[0007] In an optional embodiment, the sodium ion battery cathode material precursor satisfies at least one of the following conditions (1)-(3):

[0008] (1) The core comprises copper oxalate;

[0009] (2) The porosity of the inner core is 0.5%-2%, and the porosity of the transition layer is 4%-8%;

[0010] (3) The inner core has a diameter of 1 μm to 4 μm, the transition layer has a thickness of 0.05 μm to 0.5 μm, and the shell layer has a thickness of 0.5 μm to 3 μm.

[0011] In an optional embodiment, the sodium ion battery cathode material precursor satisfies at least one of the following conditions (4)-(5):

[0012] (4) The molar ratio of copper element to total metal elements in the sodium ion battery positive electrode material precursor is (1:5)-(1:25);

[0013] (5) The tap density of the sodium ion battery positive electrode material precursor is 1.5 g / cm 3 -2.0g / cm 3 .

[0014] In a second aspect, the present invention provides a method for preparing a precursor of a positive electrode material for a sodium ion battery as described in the first aspect, comprising the following steps:

[0015] S1: adding a precipitant and a complexing agent to a first slurry containing micron-sized copper salt particles and copper ions, and performing a first coprecipitation reaction in a reactor to obtain a second slurry;

[0016] S2: adding a metal salt mixed solution, a precipitant and a complexing agent to the second slurry, performing a second coprecipitation reaction in a reactor, and performing solid-liquid separation, washing and drying to obtain a precursor of a positive electrode material for a sodium ion battery.

[0017] In an optional embodiment, after the first coprecipitation reaction in step S1 is completed, the temperature of the reactor is raised to 50° C.-70° C. and kept warm for 0.2 h-2 h.

[0018] In an optional embodiment, the first slurry satisfies at least one of the following conditions (6)-(7):

[0019] (6) The particle size of the micron-sized copper salt particles in the first slurry is 1 μm-4 μm;

[0020] (7) The method for preparing the first slurry comprises the following steps: introducing a copper salt solution and an oxalate solution into a reaction kettle to carry out a third coprecipitation reaction to obtain the first slurry.

[0021] In an optional embodiment, the method for preparing the sodium ion battery positive electrode material precursor satisfies at least one of the following conditions (8)-(14):

[0022] (8) The reaction temperature of the first coprecipitation reaction is 30° C.-45° C., and the reaction pH is 8.0-10.0;

[0023] (9) The precipitant is sodium hydroxide solution with a concentration of 5 mol / L-10 mol / L;

[0024] (10) The complexing agent includes at least one of ammonia water, sodium citrate, EDTA and sodium oxalate, and the concentration of the complexing agent in the reactor is maintained at 0.01 mol / L-0.5 mol / L;

[0025] (11) The metal salt mixed solution includes a nickel-iron-manganese salt mixed solution, and the concentration of metal ions in the metal salt mixed solution is 1.5 mol / L-2.2 mol / L;

[0026] (12) The reaction temperature of the second coprecipitation reaction is 30° C.-80° C., and the reaction pH is 8.0-12.0;

[0027] (13) The washing comprises rinsing with sodium hydroxide solution and pure water in sequence;

[0028] (14) The precipitating agent and the complexing agent in step S1 and step S2 are the same and / or different.

[0029] In an optional embodiment, the method for preparing the first slurry satisfies at least one of the following conditions (15)-(16):

[0030] (15) The reaction temperature of the third coprecipitation reaction is 30° C.-80° C., and the reaction pH value is 5.0-7.0;

[0031] (16) The concentration of copper ions in the copper salt solution is 1.4 mol / L-1.8 mol / L, and the concentration of oxalate in the oxalate solution is 0.25 mol / L-0.35 mol / L.

[0032] In a third aspect, the present invention provides a positive electrode material obtained by mixing the sodium ion battery positive electrode material precursor and a sodium source and then calcining them, or by mixing the sodium ion battery positive electrode material precursor prepared according to the preparation method and a sodium source and then calcining them.

[0033] In a fourth aspect, the present invention provides a battery comprising the positive electrode material.

[0034] The present invention has the following beneficial effects:

[0035] (1) Compared with the hydroxide precursors of the existing sodium ion battery technology, which generally have a loose hollow structure inside, the sodium ion positive electrode material precursor provided by the present invention has a structure of a dense core, a loose transition layer and a loose shell layer, and has a higher tap density, thereby improving the energy density of the corresponding sodium ion battery.

[0036] The porosity of the dense inner core of the sodium ion positive electrode material precursor is less than that of the loose transition layer, and the transition layer has more pores. On the one hand, the pores are conducive to the attachment and growth of nickel iron manganese hydroxide; on the other hand, the existence of the pores facilitates the migration of transition metals during the sintering process of preparing the sodium positive electrode material, thereby improving the uniformity of element distribution of the sodium positive electrode material and improving the electrical performance of the corresponding sodium ion battery.

[0037] (2) The present invention adopts a segmented co-precipitation method to prepare a sodium ion positive electrode material precursor, and utilizes different co-precipitation conditions to synthesize a sodium ion battery positive electrode material precursor with a core-shell structure and high tap density.

[0038] First, a dense copper oxalate core is obtained by coprecipitation reaction; unreacted copper ions are used to coprecipitate with a precipitant to grow flaky copper hydroxide in situ on the copper oxalate core; the temperature is raised to partially or completely decompose the copper hydroxide into copper oxide to form pores and obtain a loose transition layer; and nickel-iron-manganese hydroxide is grown in situ on the loose transition layer by coprecipitation reaction. Since the transition layer is a loose flaky structure, it can be well connected with the flaky nickel-iron-manganese hydroxide, and cracks are not easy to appear, thereby improving the compatibility of the two phases. The preparation method relies on existing production processes and equipment, and is easy to operate and implement. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 is a scanning electron microscope image of the copper oxalate obtained in Example 1 of the present invention;

[0041] Figure 2 This is a scanning electron microscope image of the sodium ion battery positive electrode material precursor obtained in Example 1 of the present invention;

[0042] Figure 3 This is a cross-sectional scanning electron microscope image of the sodium ion battery positive electrode material precursor obtained in Example 1 of the present invention;

[0043] Figure 4 is an X-ray diffraction pattern of the sodium ion battery positive electrode material precursor obtained in Example 1 of the present invention;

[0044] Figure 5 This is a scanning electron microscope image of the sodium ion battery positive electrode material precursor obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0046] The following is a detailed description of the sodium ion battery positive electrode material precursor, the preparation method thereof, the positive electrode material and the battery provided by the present invention.

[0047] At present, in order to improve the uniformity of the distribution of copper elements in the positive electrode materials of sodium ion batteries, technicians choose to introduce copper ions when preparing the positive electrode material precursor to prepare nickel iron manganese copper hydroxide. However, due to the reasons that the precipitation coefficient and crystal structure of copper hydroxide are not compatible with nickel iron manganese hydroxide, the nickel iron manganese copper hydroxide product prepared by the conventional coprecipitation method has more lattice defects, high impurity content and low tap density. In order to solve the above technical problems, the present invention proposes the following technical solutions.

[0048] The present invention provides a sodium ion battery positive electrode material precursor, which comprises a core, a transition layer and a shell layer, wherein the porosity of the core is smaller than that of the transition layer, the transition layer comprises copper oxide, and the shell layer comprises nickel-iron-manganese hydroxide.

[0049] In some embodiments, the inner core of the sodium ion battery positive electrode material precursor is copper oxalate, or it may be other micron-sized copper salt particles with a dense internal structure (with low porosity). When the inner core has a low porosity, it means that the density of the inner core is relatively high, which can improve the overall tap density of the sodium ion battery positive electrode material precursor. In some embodiments, the porosity of the inner core of the sodium ion battery positive electrode material precursor is 0.5%-2%, and the porosity of the transition layer is 4%-8%. When the porosity of the inner core of the sodium ion battery positive electrode material precursor is 0.5%-2%, the sodium ion battery positive electrode material precursor has a higher tap density; when the porosity of the transition layer is 4%-8%, it is conducive to the attachment and growth of nickel iron manganese hydroxide in the transition layer, and the connection is tight.

[0050] In some embodiments, the molar ratio of copper element to total metal elements in the sodium ion battery positive electrode material precursor is (1:5)-(1:25).

[0051] In some embodiments, the tap density of the sodium ion battery cathode material precursor is 1.5 g / cm 3 -2.0g / cm 3 ;

[0052] In some embodiments, the core diameter of the sodium ion battery positive electrode material precursor is 1 μm-4 μm, the transition layer thickness is 0.05 μm-0.5 μm, and the shell layer thickness is 0.5 μm-3 μm.

[0053] In some embodiments, the carbon content of the sodium ion battery positive electrode material precursor is 0.7 wt %-5 wt %.

[0054] Accordingly, the present invention provides a method for preparing a sodium ion battery cathode material precursor, comprising the following steps:

[0055] S1: adding a precipitant and a complexing agent to a first slurry containing micron-sized copper salt particles and copper ions, and performing a first coprecipitation reaction in a reactor to obtain a second slurry;

[0056] S2: adding a metal salt mixed solution, a precipitant and a complexing agent to the second slurry, performing a second coprecipitation reaction in a reactor, and performing solid-liquid separation, washing and drying to obtain a precursor of a positive electrode material for a sodium ion battery.

[0057] Specifically, the present invention will explain each of the above steps one by one.

[0058] In some embodiments, the coprecipitation reaction mentioned in the present invention is carried out under a protective atmosphere.

[0059] In some embodiments, the stirring speed of the coprecipitation reaction mentioned in the present invention is 200 rpm-600 rpm, for example, it can be any one of 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm or a range between any two of them.

[0060] In some embodiments, the precipitant is sodium hydroxide solution with a concentration of 5 mol / L-10 mol / L, for example, any one of 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L or a range between any two of them.

[0061] In some embodiments, the complexing agent includes at least one of ammonia water, sodium citrate, EDTA and sodium oxalate, and the concentration of the complexing agent in the reactor is maintained at 0.01mol / L-0.5mol / L, for example, it can be any one of 0.01mol / L, 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L or a range value between any two of them.

[0062] In some embodiments, in steps S1 and S2, the precipitating agent and the complexing agent used may be the same or different.

[0063] In some embodiments, after the first coprecipitation reaction in step S1 is completed, the temperature of the reactor is also increased to 50°C-70°C, for example, it can be any one of 50°C, 55°C, 60°C, 65°C, 70°C or a range between any two of them; and the temperature is kept for 0.2h-2h, for example, it can be any one of 0.2h, 0.5h, 1h, 2h or a range between any two of them.

[0064] In some embodiments, the end of the first coprecipitation reaction means that the copper ion concentration in the reaction kettle no longer changes.

[0065] The copper ions in the first slurry and the precipitant sodium hydroxide undergo a coprecipitation reaction to generate flaky copper hydroxide attached to the inner core of the micron-sized copper salt particles. Copper hydroxide is very easy to decompose into copper oxide when heated. Therefore, after the first coprecipitation reaction is completed, the temperature is raised to 50°C-70°C, and the copper hydroxide is completely or partially decomposed into copper oxide. The product still maintains a flaky morphology, but the decomposition will form more pores, which is beneficial to the migration of transition metals during the sintering process of preparing sodium positive electrode materials, thereby improving the uniformity of element distribution of sodium positive electrode materials.

[0066] In some embodiments, the particle size of the micron-sized copper salt particles in step S1 is 1 μm-4 μm, for example, it can be any one of 1 μm, 2 μm, 3 μm, 4 μm or a range value between any two. The micron-sized copper salt particles need to reach a certain particle size in order to obtain the core-shell structure sodium ion battery positive electrode material precursor of the required particle size and proportion, and to ensure the uniform distribution of metal elements when the positive electrode material is made. If the particle size of the micron-sized copper salt particles is too small, the particle size of the precursor of the positive electrode material of the sodium ion battery will be too small, which will cause the precursor of the positive electrode material of the sodium ion battery and the sodium source to be easily agglomerated during sintering, and cannot be fully contacted with the electrolyte, affecting the electrochemical performance. If the particle size of the micron-sized copper salt particles is too large, it will cause the metal elements to not diffuse evenly during the sintering of the precursor of the positive electrode material of the sodium ion battery and the sodium source, resulting in poor uniformity of elements in the prepared positive electrode material.

[0067] In some embodiments, the method for preparing the first slurry in step S1 includes the following steps: introducing a copper salt solution and an oxalate solution into a reactor for a third co-precipitation reaction, and stopping feeding when the copper oxalate reaches a certain particle size to obtain the first slurry.

[0068] In some embodiments, the reaction temperature of the third coprecipitation reaction is 30°C-80°C, for example, it can be any one of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or a range value between any two of them; the reaction pH value of the third coprecipitation reaction is 5.0-7.0, for example, it can be any one of 5.0, 5.5, 6.0, 6.5, 7.0, or a range value between any two of them.

[0069] In some embodiments, the concentration of copper ions in the copper salt solution is 1.4mol / L-1.8mol / L, for example, it can be any one of 1.4mol / L, 1.5mol / L, 1.6mol / L, 1.7mol / L, 1.8mol / L, or a range between any two thereof. The concentration of oxalate in the oxalate solution is 0.25-0.35mol / L, for example, it can be any one of 0.25mol / L, 0.28mol / L, 0.30mol / L, 0.32mol / L, 0.35mol / L, or a range between any two thereof.

[0070] A low-concentration oxalate solution is prepared to make its pH neutral. Therefore, even if the oxalate is excessive in the third coprecipitation reaction, the pH of the third coprecipitation reaction system is still low at 5.0-7.0, which fails to reach the ideal precipitation pH condition and the precipitation reaction is incomplete. In addition, since the solubility product constant of copper oxalate itself is relatively large, 10%-40% of the copper ions in the copper source solution fail to precipitate during the third coprecipitation reaction and remain in a free state, thereby obtaining a first slurry containing copper oxalate particles and copper ions.

[0071] In some embodiments, the reaction temperature of the first coprecipitation reaction is 30°C-45°C, for example, it can be any one of 30°C, 35°C, 40°C, 45°C, or a range value between any two of them; the reaction pH of the first coprecipitation reaction is 8.0-10.0, for example, it can be any one of 8.0, 8.5, 9.0, 9.5, 10.0, or a range value between any two of them.

[0072] A precipitant and a complexing agent are added to the first slurry containing micron-sized copper salt particles and copper ions to carry out a first coprecipitation reaction, and copper hydroxide grows on the micron-sized copper salt particles. The surface of the micron-sized copper salt particles adsorbs hydroxide to form active sites, which can be attached to grow lamellar copper hydroxide.

[0073] Step S2: Add a metal salt mixed solution, a precipitant and a complexing agent to the second slurry to carry out a second coprecipitation reaction to prepare a shell layer. During the reaction, a portion of the clear liquid is continuously extracted with a concentrator until the molar ratio of the total metal element to the copper element reaches a preset ratio, and then the addition of the metal salt mixed solution is stopped. Subsequently, the system in the reactor is separated from the solid and liquid, washed, and dried to obtain the sodium ion battery positive electrode material precursor.

[0074] In some embodiments, the metal salt mixed solution includes a nickel, iron and manganese salt mixed solution, and the concentration of the metal salt mixed solution is 1.5 mol / L-2.2 mol / L, for example, it can be any one of 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2.0 mol / L, 2.1 mol / L, 2.2 mol / L or a range value between any two of them.

[0075] In some embodiments, the reaction temperature of the second coprecipitation reaction is 30°C-80°C, for example, it can be any one of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, or a range value between any two of them; the reaction pH of the second coprecipitation reaction is 8.0-12.0, for example, it can be any one of 8.0, 9.0, 10.0, 11.0, 12.0, or a range value between any two of them.

[0076] A nickel-iron-manganese salt mixed solution, a precipitant and a complexing agent are added to the second slurry to carry out a second coprecipitation reaction, and nickel-iron-manganese hydroxide is generated on the copper hydroxide and / or copper oxide coated copper oxalate. The flaky copper hydroxide and / or copper oxide serves as a transition layer, which is conducive to the attachment and growth of the flaky nickel-iron-manganese hydroxide thereon.

[0077] In some embodiments, the washing is to separate the solid and liquid to obtain a solid product, and then rinse it with sodium hydroxide solution and pure water in sequence.

[0078] The invention provides a positive electrode material, which is obtained by mixing the positive electrode material precursor of a sodium ion battery with a sodium source and then calcining the mixture.

[0079] The features and performance of the present invention are further described in detail below in conjunction with the accompanying drawings, examples and comparative examples. It should be understood that these examples are only used to illustrate the present application and are not used to limit the scope of the present application.

[0080] Example 1

[0081] This embodiment provides a sodium ion battery positive electrode material precursor, and the preparation method includes:

[0082] Preparation of copper oxalate core: Under nitrogen protective atmosphere, 1.6 mol / L copper sulfate solution and 0.3 mol / L sodium oxalate solution were simultaneously introduced into the reactor, the stirring speed was set to 500 rpm, and the third coprecipitation reaction was carried out to generate copper oxalate. When the particle size of the copper oxalate particles reached 2 μm, the feeding was stopped to obtain the first slurry.

[0083] The reaction pH of the third coprecipitation reaction was 6.5 and the reaction temperature was 50°C.

[0084] Preparation of copper hydroxide and / or copper oxide transition layer: sodium hydroxide solution (10 mol / L) and ammonia water are added to the first slurry to carry out a first coprecipitation reaction, and copper hydroxide is generated on the surface of copper oxalate. When the concentration of copper ions in the reactor no longer changes, the temperature of the reactor is raised to 60°C and kept warm for 1 hour to obtain a second slurry containing copper hydroxide and / or copper oxide coated with copper oxalate.

[0085] The reaction pH of the first coprecipitation reaction was 8.5, the reaction temperature was 40° C., and the concentration of ammonia in the reactor system was 0.03 mol / L.

[0086] Preparation of nickel-iron-manganese hydroxide shell: nickel sulfate, ferrous sulfate and manganese sulfate are weighed, and a 1.8 mol / L nickel-iron-manganese salt mixed solution is prepared according to the nickel-iron-manganese element molar ratio of 1: 1: 1. The nickel-iron-manganese salt mixed solution, sodium hydroxide solution (10 mol / L) and ammonia water are added to the second slurry, and a second coprecipitation reaction is carried out to prepare the nickel-iron-manganese hydroxide shell. During the reaction, part of the clear liquid is continuously pumped away with a concentrator, and the pumping flow is close to the liquid inlet flow. When the molar ratio of nickel, iron, manganese and copper elements reaches 0.3: 0.3: 0.3: 0.1 (i.e., the molar amount of copper element and total metal element is 1: 10), stop feeding. The system solid-liquid separation in the reactor obtains a solid product, and the solid product is rinsed with sodium hydroxide solution and pure water in turn, and the sodium ion battery positive electrode material precursor of the present embodiment 1 is obtained by drying.

[0087] The reaction pH of the second coprecipitation reaction was 11.0, the reaction temperature was 60° C., and the concentration of ammonia in the reactor system was 0.12 mol / L.

[0088] Instructions attached Figure 1 The scanning electron microscope image of the copper oxalate prepared in Example 1 shows that the copper oxalate is a dense block with no pores on the surface.

[0089] Instructions attached Figure 2 and attached Figure 3 The scanning electron microscope image and cross-sectional scanning electron microscope image of the sodium ion battery positive electrode material precursor prepared in this embodiment 1 show that the sodium ion battery positive electrode material precursor includes a core, a transition layer and a shell layer. The copper oxalate as the core is denser, and there is a layer of copper hydroxide and / or copper oxide as a close connection between the core copper oxalate and the shell nickel iron manganese hydroxide, and the porosity of the core is significantly smaller than that of the transition layer. The nickel iron manganese hydroxide as the shell layer has more fine pores, and because the reaction system changes due to multiple extractions of the clear liquid, a 1-3 layer ring structure appears.

[0090] Instructions attached Figure 4The X-ray diffraction pattern of the sodium ion battery positive electrode material precursor prepared in this Example 1 shows the diffraction peaks of copper oxalate and copper oxide, which proves that the synthesized sodium ion battery positive electrode material precursor contains copper oxalate and copper oxide.

[0091] Example 2

[0092] This embodiment provides a sodium ion battery positive electrode material precursor, and the preparation method includes:

[0093] Preparation of copper oxalate core: Under nitrogen atmosphere, 1.8 mol / L copper sulfate solution and 0.35 mol / L sodium oxalate solution were simultaneously introduced into the reactor for the third coprecipitation reaction, with a stirring speed of 500 rpm. When the particle size of the copper oxalate particles generated in the reactor reached 2.4 μm, the feeding was stopped to obtain the first slurry.

[0094] The reaction pH of the third coprecipitation reaction was 5.0 and the reaction temperature was 80°C.

[0095] Preparation of copper hydroxide and / or copper oxide transition layer: sodium hydroxide solution (5 mol / L) and sodium citrate solution are added to the first slurry at the same time to carry out a first coprecipitation reaction to generate copper hydroxide on the surface of copper oxalate. When the concentration of copper ions in the reactor no longer changes, the temperature of the reactor is raised to 70°C and kept warm for 0.5h to obtain a second slurry containing copper hydroxide and / or copper oxide coated with copper oxalate.

[0096] The reaction pH of the first coprecipitation reaction was 8.0, the reaction temperature was 30° C., and the concentration of sodium citrate in the reactor system was 0.01 mol / L.

[0097] Preparation of nickel-iron-manganese hydroxide shell: nickel sulfate, ferrous sulfate and manganese sulfate are weighed, and a 2.2 mol / L nickel-iron-manganese salt mixed solution is prepared according to the nickel-iron-manganese element molar ratio of 0.4: 0.2: 0.4. The nickel-iron-manganese salt mixed solution, sodium hydroxide solution (5 mol / L) and sodium citrate solution are added to the second slurry, and a second coprecipitation reaction is performed to prepare a nickel-iron-manganese hydroxide shell. During the reaction, part of the clear liquid is continuously pumped away with a concentrator, and the pumping flow rate is close to the liquid inlet flow rate. When the element molar ratio of nickel, iron, manganese and copper is 0.32: 0.16: 0.32: 0.2 (i.e., the molar amount of copper element and total metal element is 1: 5), stop feeding. The system solid-liquid separation in the reactor obtains a solid product, and the solid product is rinsed with sodium hydroxide solution and pure water in turn, and the sodium ion battery positive electrode material precursor of the present embodiment 2 is obtained by drying.

[0098] The reaction pH of the second coprecipitation reaction was 8.0, the reaction temperature was 80° C., and the concentration of sodium citrate in the reactor was 0.12 mol / L.

[0099] Example 3

[0100] This embodiment provides a sodium ion battery positive electrode material precursor, and the preparation method includes:

[0101] Preparation of copper oxalate core: Under nitrogen atmosphere, 1.4 mol / L copper sulfate solution and 0.25 mol / L sodium oxalate solution were simultaneously introduced into the reactor for the third coprecipitation reaction, with a stirring speed of 500 rpm. When the particle size of the copper oxalate particles generated in the reactor reached 1.4 μm, the feeding was stopped to obtain the first slurry.

[0102] The reaction pH of the third coprecipitation reaction was 7.0 and the reaction temperature was 30°C.

[0103] Preparation of copper hydroxide and / or copper oxide transition layer: sodium hydroxide solution (8 mol / L) and ammonia water are added to the first slurry at the same time to carry out a first coprecipitation reaction to generate copper hydroxide on the surface of copper oxalate. When the concentration of copper ions in the reactor no longer changes, the temperature of the reactor is raised to 50° C. and kept warm for 2 hours to obtain a second slurry containing copper hydroxide and / or copper oxide coated with copper oxalate.

[0104] The reaction pH of the first coprecipitation reaction was 10.0, the reaction temperature was 45° C., and the concentration of ammonia in the reactor system was 0.3 mol / L.

[0105] Preparation of nickel-iron-manganese hydroxide shell: nickel sulfate, ferrous sulfate and manganese sulfate are weighed, and a 1.8 mol / L nickel-iron-manganese salt mixed solution is prepared according to the nickel-iron-manganese element molar ratio of 1: 1: 1. The nickel-iron-manganese salt mixed solution, sodium hydroxide solution (10 mol / L) and ammonia water are added to the second slurry, and a second coprecipitation reaction is performed to prepare a nickel-iron-manganese hydroxide shell. During the reaction, part of the clear liquid is continuously pumped away with a concentrator, and the pumping flow is close to the liquid inlet flow. When the element molar ratio of nickel, iron, manganese and copper reaches 0.32: 0.32: 0.32: 0.04 (i.e., the molar amount of copper element and total metal element is 1: 25), stop feeding. The system solid-liquid separation in the reactor obtains a solid product, and the solid product is rinsed with sodium hydroxide solution and pure water in turn, and the sodium ion battery positive electrode material precursor of the present embodiment 3 is obtained by drying.

[0106] The reaction pH of the second coprecipitation reaction was 12.0, the reaction temperature was 30° C., and the concentration of ammonia in the reactor was 0.5 mol / L.

[0107] Example 4

[0108] This embodiment provides a precursor of a positive electrode material for a sodium ion battery. In this embodiment, when preparing the copper oxalate inner core, the feeding is stopped when the particle size of the copper oxalate particles reaches 1.5 μm. Other conditions are exactly the same as those in Example 1.

[0109] Example 5

[0110] This embodiment provides a precursor of a positive electrode material for a sodium ion battery. In this embodiment, when preparing the copper oxalate inner core, the feeding is stopped when the particle size of the copper oxalate particles reaches 3.5 μm. Other conditions are exactly the same as those in Example 1.

[0111] Example 6

[0112] This embodiment provides a precursor of a positive electrode material for a sodium ion battery. When preparing a transition layer of copper hydroxide and / or copper oxide in this embodiment, the insulation time is 0.2 h, and other conditions are exactly the same as those in Example 1.

[0113] Example 7

[0114] This embodiment provides a precursor of a positive electrode material for a sodium ion battery. When preparing a transition layer of copper hydroxide and / or copper oxide in this embodiment, the insulation time is 2 hours, and other conditions are exactly the same as those in Example 1.

[0115] Example 8

[0116] The present embodiment provides a precursor of a positive electrode material for a sodium ion battery. In the present embodiment, when preparing a nickel-iron-manganese hydroxide shell layer, the feeding is stopped when the molar ratio of nickel, iron, manganese and copper is 0.29:0.29:0.29:0.13, and the other conditions are exactly the same as those in Example 1.

[0117] Example 9

[0118] The present embodiment provides a precursor of a positive electrode material for a sodium ion battery. In the present embodiment, when preparing a nickel-iron-manganese hydroxide shell layer, the feeding is stopped when the molar ratio of nickel, iron, manganese and copper is 0.31:0.31:0.31:0.07, and the other conditions are exactly the same as those in Example 1.

[0119] Comparative Example 1

[0120] Nickel sulfate, ferrous sulfate, manganese sulfate and copper sulfate were weighed, and a 1.8 mol / L nickel-iron-manganese-copper salt mixed solution was prepared according to the molar ratio of nickel, iron, manganese and copper elements of 0.3:0.3:0.3:0.1. Under a nitrogen atmosphere, the nickel-iron-manganese-copper salt mixed solution, sodium hydroxide solution (10 mol / L) and ammonia water were simultaneously introduced into a reactor for coprecipitation reaction at a stirring speed of 500 rpm. The particle size of the solid product generated in the reactor reached 4.3 μm, and the feeding was stopped. The system in the reactor was separated into solid and liquid to obtain a solid product, and the solid product was rinsed with sodium hydroxide solution and pure water in turn, and dried to obtain the sodium ion battery positive electrode material precursor of this comparative example 1.

[0121] The reaction pH of the coprecipitation was 11.0, the reaction temperature was 60°C, and the concentration of ammonia in the reactor was 0.12 mol / L.

[0122] Instructions attached Figure 5 From the scanning electron microscope image of the sodium ion battery positive electrode material precursor prepared in Comparative Example 1, it can be seen that the pores are not only numerous but also relatively large, and the overall density is poor.

[0123] Comparative Example 2

[0124] This comparative example provides a sodium ion battery positive electrode material precursor. In the step of preparing a copper hydroxide and / or copper oxide transition layer, the concentration of copper ions in the reaction kettle does not change, the temperature does not increase, and other conditions are exactly the same as those in Example 1.

[0125] Test Example 1: Particle Size Distribution

[0126] The particle size and distribution of the precursor of the positive electrode material for sodium ion batteries were tested by a laser particle size analyzer. The particle size test results were expressed in terms of the median particle size D50. The test results are shown in Table 1.

[0127] Test Example 2: Porosity and layer thickness test

[0128] The surface of the material sample was bombarded with an argon ion beam to obtain a cross-sectional sample, and the internal structure of the sample was observed and analyzed with a scanning electron microscope (SEM) to obtain a cross-sectional SEM image. The threshold of the SEM image was adjusted using Image J software, the pores were selected to extract the pore area, and the porosity was calculated. The thickness of each layer of the cross-sectional sample was observed using a transmission electron microscope.

[0129] The test results are shown in Table 1.

[0130] Test Example 3: Tap density test

[0131] After the sample is fully ground, the tap density (g / cm 3 ) was tested, and the test results are shown in Table 2.

[0132] Test Example 4: Electrical Performance Test

[0133] The sodium ion battery positive electrode material precursors obtained in Examples 1-9 and Comparative Examples 1-2 were independently mixed with sodium carbonate according to the element molar ratio (Ni+Fe+Mn+Cu):Na=1:1.05, calcined at 850°C in a muffle furnace for 15h, and then crushed and sieved to obtain the positive electrode material after cooling.

[0134] The positive electrode material, carbon black and polyvinylidene fluoride were mixed into a slurry in a ratio of 0.85:0.1:0.05, coated on copper foil and vacuum dried, and then cut into positive electrode sheets with a diameter of 12 mm. The negative electrode was a metal sodium sheet, and the electrolyte was 1 mol / L sodium hexafluorophosphate. They were assembled into button cells and charged and discharged at 0.1C and 1.5-4.0V for 50 cycles.

[0135] The test results are shown in Table 2.

[0136] Table 1

[0137]

[0138]

[0139] Table 2

[0140]

[0141]

[0142] From Table 1 and Table 2, in combination with Example 1 and Comparative Example 1, it can be seen that the element molar ratio and D50 of the sodium ion battery positive electrode material precursor are not much different, but the tap density of Example 1 is 1.72, which is much higher than 0.84 of Comparative Example 1, so that the discharge capacity, first efficiency and capacity retention rate after 50 cycles of Example 1 are better than those of Comparative Example 1.

[0143] Combining Examples 1, 6-7 and Comparative Example 2, it can be seen that after the second coprecipitation, the holding time of the elevated temperature affects the tap density of the positive electrode material precursor for the sodium ion battery. The longer the holding time, the more copper hydroxide decomposes, and the more pores are left, so that the tap density of the positive electrode material precursor for the sodium ion battery is smaller.

[0144] In combination with Examples 1, 4-5 and 8-9, it can be seen that the particle size of copper oxalate particles and the molar ratio of metal elements in the precursor of the positive electrode material of a sodium ion battery will affect the particle size of the precursor of the positive electrode material of a sodium ion battery and the electrical properties of the sodium positive electrode material made therefrom. When the molar ratio of metal elements in the precursor of the positive electrode material of a sodium ion battery is the same, the smaller the particle size of the copper oxalate particles, the smaller the particle size of the precursor of the positive electrode material of a sodium ion battery; the larger the particle size of the copper oxalate particles, the larger the particle size of the precursor of the positive electrode material of a sodium ion battery, but the worse the distribution uniformity of the metal elements when the sodium positive electrode material is made, the worse the cycle performance. When the particle size of the copper oxalate particles is the same, the smaller the ratio of the total molar amount of copper elements to the metal elements, the higher the capacity of the obtained sodium positive electrode material and the worse the cycle performance; the larger the ratio of the total molar amount of copper elements to the metal elements, the lower the capacity of the obtained sodium positive electrode material and the better the cycle performance.

[0145] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A sodium ion battery cathode material precursor, characterized in that: The sodium ion battery positive electrode material precursor comprises a core, a transition layer and a shell layer, the porosity of the core is less than the porosity of the transition layer, the transition layer comprises copper oxide, and the shell layer comprises nickel iron manganese hydroxide.

2. The sodium ion battery cathode material precursor according to claim 1, characterized in that: The sodium ion battery positive electrode material precursor satisfies at least one of the following conditions (1)-(3): (1) The core comprises copper oxalate; (2) The porosity of the inner core is 0.5%-2%, and the porosity of the transition layer is 4%-8%; (3) The inner core has a diameter of 1 μm to 4 μm, the transition layer has a thickness of 0.05 μm to 0.5 μm, and the shell layer has a thickness of 0.5 μm to 3 μm.

3. The sodium ion battery positive electrode material precursor according to claim 1, characterized in that: The sodium ion battery positive electrode material precursor satisfies at least one of the following conditions (4)-(5): (4) The molar ratio of copper element to total metal elements in the sodium ion battery positive electrode material precursor is (1:5)-(1:25); (5) The tap density of the sodium ion battery positive electrode material precursor is 1.5 g / cm 3 -2.0g / cm 3 .

4. A method for preparing a precursor of a positive electrode material for a sodium ion battery according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: adding a precipitant and a complexing agent to a first slurry containing micron-sized copper salt particles and copper ions, and performing a first coprecipitation reaction in a reactor to obtain a second slurry; S2: adding a metal salt mixed solution, a precipitant and a complexing agent to the second slurry, performing a second coprecipitation reaction in a reactor, and performing solid-liquid separation, washing and drying to obtain a precursor of a positive electrode material for a sodium ion battery.

5. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 4, characterized in that: After the first coprecipitation reaction is completed, step S1 also includes raising the temperature of the reactor to 50° C.-70° C. and keeping it warm for 0.2 h-2 h.

6. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 4, characterized in that: The first slurry satisfies at least one of the following conditions (6)-(7): (6) The particle size of the micron-sized copper salt particles in the first slurry is 1 μm-4 μm; (7) The method for preparing the first slurry comprises the following steps: introducing a copper salt solution and an oxalate solution into a reaction kettle to carry out a third coprecipitation reaction to obtain the first slurry.

7. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 4, characterized in that: The preparation method satisfies at least one of the following conditions (8)-(14): (8) The reaction temperature of the first coprecipitation reaction is 30° C.-45° C., and the reaction pH is 8.0-10.0; (9) The precipitant is sodium hydroxide solution with a concentration of 5 mol / L-10 mol / L; (10) The complexing agent includes at least one of ammonia water, sodium citrate, EDTA and sodium oxalate, and the concentration of the complexing agent in the reactor is maintained at 0.01 mol / L-0.5 mol / L; (11) The metal salt mixed solution includes a nickel-iron-manganese salt mixed solution, and the concentration of metal ions in the metal salt mixed solution is 1.5 mol / L-2.2 mol / L; (12) The reaction temperature of the second coprecipitation reaction is 30° C.-80° C., and the reaction pH is 8.0-12.0; (13) The washing comprises rinsing with sodium hydroxide solution and pure water in sequence; (14) The precipitant and the complexing agent in S1 and S2 are the same and / or different.

8. The method for preparing a precursor of a positive electrode material for a sodium ion battery according to claim 6, characterized in that: The method for preparing the first slurry satisfies at least one of the following conditions (15)-(16): (15) The reaction temperature of the third coprecipitation reaction is 30° C.-80° C., and the reaction pH value is 5.0-7.0; (16) The concentration of copper ions in the copper salt solution is 1.4 mol / L-1.8 mol / L, and the concentration of oxalate in the oxalate solution is 0.25 mol / L-0.35 mol / L.

9. A positive electrode material, characterized in that: The positive electrode material precursor of the sodium ion battery according to any one of claims 1 to 3 is mixed with a sodium source and then calcined, or the positive electrode material precursor of the sodium ion battery obtained by the preparation method according to any one of claims 4 to 8 is mixed with a sodium source and then calcined.

10. A battery, characterized in that: Comprising the positive electrode material according to claim 9.

Citation Information

Cited By

  • Sodium-ion battery positive electrode material with core-shell structure and preparation method of sodium-ion battery positive electrode material

    CN120784312A